2008
DOI: 10.1111/j.1600-0854.2008.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus‐6 Induces MVB Formation, and Virus Egress Occurs by an Exosomal Release Pathway

Abstract: †These authors contributed equally to this work.The final envelopment of most herpesviruses occurs at Golgi or post-Golgi compartments, such as the trans Golgi network (TGN); however, the final envelopment site of human herpesvirus 6 (HHV-6) is uncertain. In this study, we found novel pathways for HHV-6 assembly and release from T cells that differed, in part, from those of alphaherpesviruses. Electron microscopy showed that late in infection, HHV-6-infected cells were larger than uninfected cells and containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
172
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(177 citation statements)
references
References 63 publications
2
172
3
Order By: Relevance
“…pH 7.2, for immunoelectron microscopy (27). In the former procedure the cells were post-fixed with 1% OsO 4 and embedded in Epon 812 after dehydration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…pH 7.2, for immunoelectron microscopy (27). In the former procedure the cells were post-fixed with 1% OsO 4 and embedded in Epon 812 after dehydration.…”
Section: Methodsmentioning
confidence: 99%
“…2A), we speculated that the cleavage site was located in the N-terminal region. Therefore, we performed Edman degradation analysis of the lower band of PGAM5 and determined that its N-terminal sequence was Ala-Val-Ala-Val-Gly (amino acids [25][26][27][28][29]. This suggested that the lower band of PGAM5 was a processed form and that the cleavage site was located in the TM domain (Fig.…”
Section: Pgam5 Is An Imm-resident Protein Phosphatase-pgam5mentioning
confidence: 99%
“…MVBs contain CD63, which is an MVB late endosome marker and envelope glycoprotein, that is localized in internal vesicles. The available evidence indicates that HHV-6 virions are released through the exosomal pathway, which demonstrates the significance of exosomes in the HHV6 maturation pathway (Mori et al, 2008). Additionally, MHC class I molecules are another rare member that have been found to be inserted into viral particles and exosomes and then released into the extracellular space via an exosomal secretary pathway, which can be blocked by the U24 protein of HHV-6 (Sullivan and Coscoy, 2010;Ota et al, 2014).…”
Section: Exosomes In Beta Herpesvirus Infectionmentioning
confidence: 99%
“…These exosomes are derived from MVBs. The route of exosomal release may also be targeted by viral proteins (21). A release of gB and of gB-DR complexes by exosomes could demonstrate a novel route for the HSV-1-encoded gB and of gB-associated DR. To elucidate some details of trafficking in the endocytic pathway, we investigated whether MJ cells secrete exosomes.…”
Section: Release Of Gb-dr Complexes Via Exosomesmentioning
confidence: 99%